Increasing Children's Intelligence through the STEAM Learning Model in Elementary School - Gusmaniarti Gusmaniarti; Berda Asmara; Mochamad Nursalim; Diana Rahmasari (EDUTEC : Journal of Education And Technology, 2023)
STEAM, an acronym for Science, Technology, Engineering, Arts, and Mathematics, represents an instructional approach closely linked to children's cognitive abilities. The combination of science, technology, engineering, mathematics, and arts in the learning process can prepare students with 21st-century skills. The objective of this study is to examine the STEAM learning model in primary education through a literature review, aiming to enhance students' intelligence. This research is qualitative in nature, utilizing a literature review to connect existing research and fill gaps in prior studies. The findings of this study reveal that the STEAM learning model for children can be implemented by creating a safe and enjoyable learning environment. It provides children with opportunities for exploration, discovery, construction, experimentation, prediction, seeking answers to complex questions, and connecting knowledge to real-life situations, thereby stimulating their intelligence.